Career Development of Young Physician–Scientists in the Cardiovascular Sciences: Perspective and Advice From the Early Career Committee of the Cardiopulmonary, Critical Care, and Resuscitation Council of the American Heart Association. Issue 10 (11th May 2018) - Agarwal, Sachin; Spiekerkoetter, Edda; Austin, Eric D.; de Jesus Perez, Vinicio; Dezfulian, Cameron; Maron, Bradley A.; Ryan, John J.; Starks, Monique A.; Yu, Paul B.; Bonnet, Sebastien; Perman, Sarah M.
Abstract : Supplemental Digital Content is available in the text.